Vietnam’s Perception and Response to the Emerging Indo-Pacific Regional Security Architecture - Linh Do Khuong Manh (Ilomata International Journal of Social Science, 2022)
With the rising of the two emerging great power - China and India, the "Indo-Pacific" has already possessed the fundamental conditions of the regional security complex, while the United States as the hegemonic state intervenes in security affairs which takes advantage of characteristics of the identity structure and power structure of regional security complexes by penetration mechanism. Buzan's theory has shown us the contour of the emerging security architecture in the Indo-Pacific region. After applying the regional security complex theory to analyze the security of the region, this article analyzes Vietnam’s perception and response to the emerging Indo-Pacific security architecture. The article points out that the perception of regional security structure expressed through foreign policy adjustment can be basically divided into two layers: regional and extra-regional. In which the regional layer with the focus on ASEAN; and the extra-regional is ASEAN-centered multilateral groups. Since then, Vietnam has tried to incorporate its foreign policy calculations into the multilateral and multi-dimensional Indo-Pacific agenda. Vietnam's response manifests itself mainly in strengthening economic and trade cooperation with China, deepening security cooperation with the US and its network of allies, and with the help of the power of ASEAN to restrain the US and China. In addition, with its favorable geographical position and strong rise in recent years, Vietnam expects India to become an indispensable "security supplier" and an indispensable "balancing force" in Indo-Pacific regional security architecture.